1981
DOI: 10.1021/bi00512a010
|View full text |Cite
|
Sign up to set email alerts
|

Production and isolation of siderophores from the soil fungus Epicoccum purpurascens

Abstract: A large number of iron transport agents, siderophores, which stimulated the growth of Arthrobacter flavescens JG-9, were isolated during a study of the antitumor activity associated with the metabolic products of the fungus Epicoccum purpurascens. The production of the siderophores was significantly enhanced in a variety of media by culture of the fungus in the near absence of ferric iron. A novel method of purification involving a carboxylic ion-exchange resin separated the siderophores into four subgroups. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

1986
1986
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 10 publications
0
28
0
2
Order By: Relevance
“…contaminated with seed mieroflora and microorganisms introduced by routine handling), with similar plants that were additionally inoculated with a soil suspension (garden soil, Universitfit Hohenheim) or a root-colonizing bacterium, Arthrobacter flavescens JG-9 (Aureobacterium flavescens, ATCC 13348). The latter bacterial inoculum was produced as a 48-hr culture in Arthrobacter assay medium (Frederick et al, 1981) agitated at 100 rpm on a rotary shaker at 27°C, and was added at a rate of 5 ml per 3-L container 3 days prior to the uptake experiment. Other plants were inoculated with 5 mL of a mixed soil inoculum obtained from a soil:water (2:1) suspension filtrate passed through Whatman no.…”
Section: Microbial Inoculation Of Plantsmentioning
confidence: 99%
“…contaminated with seed mieroflora and microorganisms introduced by routine handling), with similar plants that were additionally inoculated with a soil suspension (garden soil, Universitfit Hohenheim) or a root-colonizing bacterium, Arthrobacter flavescens JG-9 (Aureobacterium flavescens, ATCC 13348). The latter bacterial inoculum was produced as a 48-hr culture in Arthrobacter assay medium (Frederick et al, 1981) agitated at 100 rpm on a rotary shaker at 27°C, and was added at a rate of 5 ml per 3-L container 3 days prior to the uptake experiment. Other plants were inoculated with 5 mL of a mixed soil inoculum obtained from a soil:water (2:1) suspension filtrate passed through Whatman no.…”
Section: Microbial Inoculation Of Plantsmentioning
confidence: 99%
“…9,11 It is interesting that 3 unexpectedly could not exert differential growth inhibitory activity similar to 1 and 2 (Figure 3), suggesting that N-hydroxyamide moiety at N-16 might be critical to the activity. Although the mechanisms of actions of 1 and 2 as well as that of triornicin are still unknown, they might have a similar target.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic color reaction to FeCl 3 indicated that they were a family of siderophore. 9 The molecular formulae of 1, 2 and 3 were determined to be C 18 …”
Section: Physico-chemical Propertymentioning
confidence: 99%
“…Sequestration of iron is often achieved by siderophores, a class of microbially produced organic ligands having conditional stability constants in the order of 10 19 -10 22 M )1 . Most siderophores are of two types, catecholate and hydroxamate [3,6,14,15,17,22,25,26,27,29]. …”
Section: Bioleaching Experimentsmentioning
confidence: 99%